LYMPHANGIOGENESIS IN ORAL SQUAMOUS CELL CARCINOMA AND POTENTIALLY MALIGNANT ORAL LESIONS - SAUMYA CHANDRA,; MADHU MATI GOEL,; ANNU MAKKER,; SEEMA NAYAK,; PRIYANKA SHILPI,; VIKRAM BHATIA,; M.L.B. BHATT, (International Journal of Pharma and Bio Sciences, 2014)
Podoplanin is a mucin-like glycoprotein that is important in lymphangiogenesis but not in blood vessel formation. The aim of this study is to determine the role of podoplanin in malignant transformation of PMOLs to oral cancer and in progression of oral cancer. In this report, LVD defined as of podoplanin detected positive lymphatic vessels and MVD as the density of CD-31 positive microvessels. The objectives of this study were to clarify the clinical and prognostic significance of both LVD and MVD in PMOLs and oral cancer. The current results suggested that LVD is a more useful tool than MVD. We can conclude that podoplanin is involved in malignant transformation to oral cancer in PMOLs patients and can be a predictor for lymph node metastasis in oral cancer patients.